Makna Kawe Kolo R’ete Tengu Sebagai Upacara Perdamaian Masyarakat Kelitembu dan Elemolo di Persekutuan Tana Tobi Watu Bhangu Kecamatan Wewaria Kabupaten Ende - Bata, Falentinus; Mandona, Inggrid V.G. (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
Language is a very important thing for humans. Humans cannot communicate with each other if there is no language. Humans will find it difficult to state their existence if language is not known. In other words, language is something that humans really need. Without language, human socialization activities and other life activities will be paralyzed. Given the important role of language in human life, concern for language especially, in this case Indonesian, as a national language needs to be nurtured and developed (Efendy, 2008: 80). This research was carried out with the aim of describing the meaning of Kawe Kolo rete Tengu as a Peace Ceremony for the Kelitembu and Elamelo People in the Tana Tobi Watu Bhangu Fellowship, Wewaria District, Ende Regency. This study uses a qualitative descriptive design, namely the research objectives are described factually and naturally. The methods and techniques of data collection in this study were the listening and speaking method. The techniques used in this research are note-taking techniques, recording techniques, and interview techniques. The data that has been collected is then processed or analyzed using an interactive analysis model developed by Milles and Huberman (1992). There are four components of activities carried out with this pattern, namely data collection, data reduction, data display, and finally drawing conclusions or verification. The theory used in this research is cultural linguistic theory. Thus, the study of the meaning of Kawe Kolo rete Tengu as a Peace Ceremony for the Kelitembu and Elamelo communities in the Tana Tobi Watu Bhangu Fellowship, Wewaria District, Ende Regency, is classified as a qualitative descriptive approach. The results of the study stated that the meaning of Kawe Kolo rete Tengu as a Peace Ceremony for the Kelitembu and Elamelo Community in the Tana Tobi Watu Bhangu Fellowship, Wewaria District, Ende Regency had religious meanings, togetherness meanings, welfare meanings, petition meanings, and family meanings.